PENGEMBANGAN DAN PEMANFAATAN BAHAN AJAR MODUL DALAM PROSES PEMBELAJARAN - Sungkono, Sungkono (MAJALAH ILMIAH PEMBELAJARAN, 2009)
Teachers need the competencies to develop learning material especially module, considering that the development of learning material could contribute to the efficiency and effectiveness of students learning process. Moreover, learning materials have a significant role both for teachers and students in individual learning and classical or group learning context. Learning using module has some characteristics that are, self instruction, the recognition of individual differences, including the learning objectives/competencies, the occurrence of existence, structure and knowledge order, the use of multimedia, students active participation, direct reinforcement toward students’ respond, evaluation toward students learning. In order to develop module, we need to consider some techniques and components required, such as: the course overview component, introduction, learning activities, exercises, summary, formative test, and answer key for formative test and follow up. On the other hand, to develop module we can use some techniques including starting from scratch, information repackaging, and compilation. The utilization of module in the learning process can be done in the context of both individual learning and group learning system.